Functional properties of granule cells with hilar basal dendrites in the epileptic dentate gyrus. (26th November 2016) - Kelly, Tony; Beck, Heinz
Summary: Objective: The maturation of adult‐born granule cells and their functional integration into the network is thought to play a key role in the proper functioning of the dentate gyrus. In temporal lobe epilepsy, adult‐born granule cells in the dentate gyrus develop abnormally and possess a hilar basal dendrite (HBD). Although morphological studies have shown that these HBDs have synapses, little is known about the functional properties of these HBDs or the intrinsic and network properties of the granule cells that possess these aberrant dendrites. Methods: We performed patch‐clamp recordings of granule cells within the granule cell layer "normotopic" from sham‐control and status epilepticus (SE) animals. Normotopic granule cells from SE animals possessed an HBD (SE + HBD + cells) or not (SE + HBD − cells). Apical and basal dendrites were stimulated using multiphoton uncaging of glutamate. Two‐photon Ca 2+ imaging was used to measure Ca 2+ transients associated with back‐propagating action potentials (bAPs). Results: Near‐synchronous synaptic input integrated linearly in apical dendrites from sham‐control animals and was not significantly different in apical dendrites of SE + HBD − cells. The majority of HBDs integrated input linearly, similar to apical dendrites. However, 2 of 11 HBDs were capable of supralinear integration mediated by a dendritic spike. Furthermore, the bAP‐evoked Ca 2+ transients were relatively well maintained along HBDs, compared with apical dendrites. This further suggests an enhanced electrogenesis in HBDs. In addition, the output of granule cells from epileptic tissue was enhanced, with both SE + HBD − and SE + HBD + cells displaying increased high‐frequency (>100 Hz) burst‐firing. Finally, both SE + HBD − and SE + HBD + cells received recurrent excitatory input that was capable of generating APs, especially in the absence of feedback inhibition. Significance: Taken together, these data suggest that the enhanced excitability of HBDs combined with the altered intrinsic and network properties of granule cells collude to promote excitability and synchrony in the epileptic dentate gyrus.